Physico-chemical and biological properties of dental calcium silicate cements - literature review - Ilić, Dragan V.; Antonijević, Đorđe M.; Biočanin, Vladimir M.; Čolović, Božana; Danilović, Vesna; Komlev, Vladimir S.; Teterina, Anastasia Y.; Jokanović, Vukoman R. (HEMIJSKA INDUSTRIJA (Chemical Industry), 2019)
Dental cement materials have been developed with the aim to replace hard dental tissues. The first material used for pulp capping, root canal obturation, bifurcation perforation and apexification is calcium hydroxide (in 1920). A half century later, glass-ionomer cements began to suppress it as dentine substitutes. Finally, in the 1990s, calcium silicate (CS) material appeared in the dental research community as the most promising dentine substitute capable to adequately meet all clinical requirements. The aim of this paper is to present an overview of literature related to studies about CS materials taking into account their physical, chemical and biological properties and clinical applications. This review aims to discuss beneficial and adverse characteristics of CSs concerning interactions to the hard dentine and soft pulp/periodontal tissues. This review article deals with the literature data about currently commercially available CS concerning laboratory and clinical findings. 109 scientific articles were analyzed of which 62 references reported in vitro and 26 in vivo investigations while 21 references comprised reports, reviews and books dealing with both, in vitro and in vivo investigations. Although further data collection is necessary, CSs are promising materials that represent a gold standard for numerous dental clinical procedures.